A study of vitamin D receptor gene polymorphisms and serum 25-hydroxyvitamin D levels in vitiligo patients and controls - Tonita M Noronha; Banavasi Shanmukha Girisha; Suchetha Kumari; Shilpa S Shetty; Muthtamil Sampath (Wolters Kluwer Medknow Publications, 2022)
Background: Vitiligo is a common pigmentary disorder affecting 0.1%-2% of the global population. Recently, interest has evoked in the role of Vitamin D in decreasing the risk of several chronic diseases. Little is known about the genetics of vitiligo. This study was conducted to investigate whether Vitamin D receptor (VDR) polymorphisms could be the susceptibility markers for vitiligo. Objectives: (i) To evaluate the potential association between VDR polymorphisms and vitiligo susceptibility and (ii) To estimate the serum levels of 25-hydroxyvitamin D in case and control groups. Materials and Methods: This study included 34 participants (17 with vitiligo and 17 age-and gender-matched healthy controls). After a written informed consent, a detailed history and examination was done. Serum 25(OH)D levels were measured using the enzyme-linked immunosorbent assay kit. Genomic DNA was extracted from the peripheral blood. The VDR polymorphisms were genotyped using the polymerase chain reaction-restriction fragment length polymorphism method. Fok1, Bsm1, Apa1, and Taq1 restriction enzymes were used to determine the genotypes of the respective polymorphisms. Results: Nonsegmental vitiligo was the most common type of vitiligo seen in 14 (82.4%) cases. The mean serum Vitamin D level in cases was 35.64 ± 15.68 ng/ml and in controls was 37.00 ± 16.45 (P = 0.81). There was no significant difference in the distribution of VDR polymorphisms between the case and control groups. Conclusion: In our study, no significant difference was observed in the distribution of Fok1, Bsm1, Apa1, and Taq1 VDR polymorphisms between the case and control groups. However, we observed a significant association between the Fok1 polymorphism and serum 25(OH) Vitamin D levels in vitiligo patients studied.